Advances in brain and religion studies: a review and synthesis of recent representative studies - McNamara, Patrick; Grafman, Jordan (Frontiers in Human Neuroscience, 2024)
We review and synthesize recent religion and brain studies and find that at a broad network neuroscience level, religious/spiritual experiences (RSEs) appear to depend crucially upon interactions between the default mode network (DMN), the frontoparietal network (FPN), and the salience network (SN). We see this general result as broadly consistent with Menon’s et al. “Triple Network or Tripartite Model” (TPM) of neuropsychiatric function/dysfunction. A TPM cycling model is here offered to account for details of neural bases of an array of RSE phenomena including ecstatic seizures, neuroimaging of religious participants, psychedelically induced mystical states and perceptions of supernatural agents. To adequately account for SA perceptions, however, recent evidence suggests that REM sleep and dreaming mechanisms likely play a role. Future research should examine neurodevelopmental mechanisms of acquired SA perceptions as well as societal-level effects such as brain mediated religious beliefs of in-group cohesion and out-group hostility.